Case report of a Patient with SVC syndrome in the course of pulmonary hilar and mediastinal neoplasia - Święch, Paweł; Jaźwiec, Przemysław; Bazan, Andrzej (Quality in Sport, 2025)
Superior vena cava syndrome (SVCS) is a serious clinical condition caused by obstruction of the superior vena cava, usually due to malignancies. We present a case of a 67-year-old woman with SVCS secondary to a tumour in the right pulmonary hilum and mediastinum. The patient exhibited facial and neck swelling, venous distention, and dyspnoea. Computed tomography confirmed a large polycystic mass causing complete occlusion of the superior vena cava and extensive venous thrombosis. The patient was treated with anticoagulation therapy and referred for oncological assessment. This case underscores the importance of prompt diagnosis and imaging in guiding SVCS management.